Exotica and the Ethiopian of Acts 8:26–40: Toward a Different Fabula - Aymer, Margaret P. (Journal of Biblical literature, 2023)
Scholarship on the Ethiopian eunuch focuses heavily on his foreign otherness, identifying him as the first gentile convert in the Acts of the Apostles. Such a reading tends not only to exoticize the Ethiopian but also to vilify the temple and, by extension, first-century Judaism, for their imagined rejection of this man. Using Saidiya Hartman's work on "critical fabulation," I propose instead that the Ethiopian be read as a Jew and, moreover, as an embodiment of the Jewish experiences of exile and enslavement to which his castrated body points. Such a reading supports the theme of the ingathering of dispersed Jews within the nascent Christian movement, which is central to Acts 1-8.